Strategies to Improve the Efficiency of Somatic Cell Nuclear Transfer - Srirattana, Kanokwan; Kaneda, Masahiro; Parnpai, Rangsun (International journal of molecular sciences, 2022)
Mammalian oocytes can reprogram differentiated somatic cells into a totipotent state through somatic cell nuclear transfer (SCNT), which is known as cloning. Although many mammalian species have been successfully cloned, the majority of cloned embryos failed to develop to term, resulting in the overall cloning efficiency being still low. There are many factors contributing to the cloning success. Aberrant epigenetic reprogramming is a major cause for the developmental failure of cloned embryos and abnormalities in the cloned offspring. Numerous research groups attempted multiple strategies to technically improve each step of the SCNT procedure and rescue abnormal epigenetic reprogramming by modulating DNA methylation and histone modifications, overexpression or repression of embryonic-related genes, etc. Here, we review the recent approaches for technical SCNT improvement and ameliorating epigenetic modifications in donor cells, oocytes, and cloned embryos in order to enhance cloning efficiency.